Reductions in vancomycin and meropenem following the implementation of a febrile neutropenia management algorithm in hospitalized adults: An interrupted time series analysis. (25th September 2021) - Trinh, Trang D.; Strnad, Luke; Damon, Lloyd; Dzundza, John H.; Graff, Larissa R.; Griffith, Laura M.; Hilts-Horeczko, Alexandra; Olin, Rebecca; Shenoy, Samantha; DeVoe, Catherine; Wang, Lusha; Rodriguez-Monguio, Rosa; et al.
Abstract: Objective: To evaluate broad-spectrum intravenous antibiotic use before and after the implementation of a revised febrile neutropenia management algorithm in a population of adults with hematologic malignancies. Design: Quasi-experimental study. Setting and population: Patients admitted between 2014 and 2018 to the Adult Malignant Hematology service of an acute-care hospital in the United States. Methods: Aggregate data for adult malignant hematology service were obtained for population-level antibiotic use: days of therapy (DOT), C. difficile infections, bacterial bloodstream infections, intensive care unit (ICU) length of stay, and in-hospital mortality. All rates are reported per 1, 000 patient days before the implementation of an febrile neutropenia management algorithm (July 2014–May 2016) and after the intervention (June 2016–December 2018). These data were compared using interrupted time series analysis. Results: In total, 2, 014 patients comprised 6, 788 encounters and 89, 612 patient days during the study period. Broad-spectrum intravenous (IV) antibiotic use decreased by 5.7% with immediate reductions in meropenem and vancomycin use by 22 ( P = .02) and 15 ( P = .001) DOT per 1, 000 patient days, respectively. Bacterial bloodstream infection rates significantly increased following algorithm implementation. No differences were observed in the use of other antibiotics or safety outcomes including C. difficile infection, ICU length of stay, and in-hospital mortality. Conclusions: Reductions in vancomycin and meropenem were observed following the implementation of a more stringent febrile neutropenia management algorithm, without evidence of adverse outcomes. Successful implementation occurred through a collaborative effort and continues to be a core reinforcement strategy at our institution. Future studies evaluating patient-level data may identify further stewardship opportunities in this population.